Origins and diversity of macrophages in health and disease. Issue 12 (20th December 2020) - Sreejit, Gopalkrishna; Fleetwood, Andrew J; Murphy, Andrew J; Nagareddy, Prabhakara R
Abstract: Macrophages are the first immune cells in the developing embryo and have a central role in organ development, homeostasis, immunity and repair. Over the last century, our understanding of these cells has evolved from being thought of as simple phagocytic cells to master regulators involved in governing a myriad of cellular processes. A better appreciation of macrophage biology has been matched with a clearer understanding of their diverse origins and the flexibility of their metabolic and transcriptional machinery. The understanding of the classical mononuclear phagocyte system in its original form has now been expanded to include the embryonic origin of tissue‐resident macrophages. A better knowledge of the intrinsic similarities and differences between macrophages of embryonic or monocyte origin has highlighted the importance of ontogeny in macrophage dysfunction in disease. In this review, we provide an update on origin and classification of tissue macrophages, the mechanisms of macrophage specialisation and their role in health and disease. The importance of the macrophage niche in providing trophic factors and a specialised environment for macrophage differentiation and specialisation is also discussed. Abstract : In this review, we provide a clear, comprehensive update on monocyte/ macrophage ontogeny, differentiation and function.